A comparative study of selected Asian countries on carbon emissions with respect to different trade and climate changes mitigation policy scenarios - Truong Phuoc Truong (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2010)
Trade, economic development, and climate change issues are closely linked and this has significant implications for the design of climate change policies especially for developing countries. Developing countries regard the objective of economic development and growth as being as important as the objective of climate change mitigation, and therefore prefer to use emission intensity reductions as targets for their climate change policies. In theory, this may seem to allow for both economic growth and climate change mitigation objectives to be achieved in a harmonious manner but on closer analysis, no simple choice of a policy target can help to resolve the fundamental issue of how to reconcile the objective of economic growth with the objective of climate change mitigation. In this study we look at the case of China, India, Bangladesh, Indonesia, Thailand, and Vietnam, and consider the following questions: (i) how to measure the impacts of trade and economic activities on the levels of CO2 emissions, (ii) how to measure the impacts of current climate change policies on trade and economic activities, (iii) how to improve on existing policies to better achieve the targets of economic growth while also contributing to the objectives of climate change mitigation. A general equilibrium model is used to conduct some simulations of a business as usual (BaU) and also some climate change and policy scenarios.
Keywords: Q41; Q43; Q54; Q56; Q58; 330; Climate change; CO2 emissions; Energy intensity; Emission intensity; Mitigation policies; Economic growth; Trade; Computable General equilibrium model; Asian countries